TIGAR Attenuates High Glucose-Induced Neuronal Apoptosis via an Autophagy Pathway - Zhou, Wenjuan; Yao, Yuan; Li, Jinxing; Wu, Dong; Zhao, Man; Yan, Zongting; Pang, Aimei; Kong, Liang (Frontiers in Molecular Neuroscience, 2019)
Hyperglycemia-induced neuronal apoptosis is one of the important reasons for diabetic neuropathy. Long-time exposure to high glucose accelerates many aberrant glucose metabolic pathways and eventually leads to neuronal injury. However, the underlying mechanisms of metabolic alterations remain unknown. TP53-inducible glycolysis and apoptosis regulator (TIGAR) is an endogenous inhibitor of glycolysis and increases the flux of pentose phosphate pathway (PPP) by regulating glucose 6-phosphate dehydrogenase (G6PD). TIGAR is highly expressed in neurons, but its role in hyperglycemia-induced neuronal injury is still unclear. In this study, we observed that TIGAR and G6PD are decreased in the hippocampus of streptozotocin (STZ)-induced diabetic mice. Correspondingly, in cultured primary neurons and Neuro-2a cell line, stimulation with high glucose induced significant neuronal apoptosis and down-regulation of TIGAR expression. Overexpression of TIGAR reduced the number of TUNEL-positive neurons and prevented the activation of Caspase-3 in cultured neurons. Furthermore, enhancing the expression of TIGAR rescued high glucose-induced autophagy impairment and the decrease of G6PD. Nitric oxide synthase 1 (NOS1), a negative regulator of autophagy, is also inhibited by overexpression of TIGAR. Inhibition of autophagy abolished the protective effect of TIGAR in neuronal apoptosis in Neuro-2a. Importantly, overexpression of TIGAR in the hippocampus ameliorated STZ-induced cognitive impairment in mice. Therefore, our data demonstrated that TIGAR may have an anti-apoptosis effect via up-regulation of autophagy in diabetic neuropathy.